Bile acids in the diarrhoea of ileal resection. Issue 5 (May 1973) - Mitchell, W. D.; Findlay, J. M.; Prescott, R. J.; Eastwood, M. A.; Horn, D. B.
Abstract : Twenty individual diarrhoeal stools from three patients with ileal resection were centrifuged at 14 000 g for one hour at 10°C to separate the stool into pellet and supernatant. Bile acids and electrolytes were measured in each phase. Relationships were examined between chenodeoxycholic acid and cholic acid in each phase and in toto to electrolyte and water loss. Chenodeoxycholic acid was associated with electrolyte and water loss whether present in solid or liquid phase. The association varied between individuals. The cholic acid content of the stool showed no association with electrolyte and water loss. It would appear that it is the total amount of chenodeoxycholic acid entering the colon, irrespective of its physical state, that is important in the diarrhoea of ileal dysfunction.